Character Education in Mathematics Learning in Contemporary Era: A Case Study in Indonesia - Suyitno, Hardi; Setyawan, Fariz (International Journal on Emerging Mathematics Education, 2023)
This research aimed to discover character education in the Contemporary Era. This research is qualitative phenomenological research. As the main instrument, researchers have long studied several library studies in the form of journal articles related to character education in mathematics learning in Indonesia. In addition, some descriptive data are obtained from the writer's experience studying character education over the last five years. Character development through mathematical teaching requires teachers to associate the character values they want to develop with the importance of mathematics and their learning. Then, teachers must be capable of planning and implementing their knowledge. The axiom is determined by agreement; thus, the deal is significant in mathematics. It will embed the agreement's value in the soul of every child who succeeds well when learning mathematics. Eventually, obedience will be inherited in the child's soul. A theorem is a broad range of factual statements and truths obtained from axioms using deductive reasoning. If, in mathematical learning the teacher succeeds in inserting the values contained in the relationship between theorem and axiom, the teacher can also integrate Pancasila values so that Pancasila is positioned like axioms. In short, contextual and contemporary mathematical learning plays a significant role in developing skills essential to modern society and the formation of national character.